Rht24b, an ancient variation of TaGA2ox-A9, reduces plant height without yield penalty in wheat - Xiuling Tian; Xianchun Xia; Dengan Xu; Yongqiang Liu; Li Xie; Hassan, Muhammad Adeel; Jie Song; Faji Li; Desen Wang; Yong Zhang; Yuanfeng Hao; Genying Li; et al. (Wiley, 2022)
Rht-B1b and Rht-D1b, the ‘Green Revolution’ (GR) genes, greatly improved yield potential of wheat under nitrogen fertilizer application, but reduced coleoptile length, seedling vigor and grain weight. Thus, mining alternative reduced plant height genes without adverse effects is urgently needed. We isolated the causal gene of Rht24 through map-based cloning and characterized its function using transgenic, physiobiochemical and transcriptome assays. We confirmed genetic effects of the dwarfing allele Rht24b with an association analysis and also traced its origin and distribution. Rht24 encodes a gibberellin (GA) 2-oxidase, TaGA2ox-A9. Rht24b conferred higher expression of TaGA2ox-A9 in stems, leading to a reduction of bioactive GA in stems but an elevation in leaves at the jointing stage. Strikingly, Rht24b reduced plant height, but had no yield penalty; it significantly increased nitrogen use efficiency, photosynthetic rate and the expression of related genes. Evolutionary analysis demonstrated that Rht24b first appeared in wild emmer and was detected in more than half of wild emmer and wheat accessions, suggesting that it underwent both natural and artificial selection. These findings uncover an important genetic resource for wheat breeding and also provide clues for dissecting the regulatory mechanisms underlying GA-mediated morphogenesis and yield formation.